PERAN PERANGKAT DESA DALAM AKUNTABILITAS PENGELOLAAN DANA DESA - Kurnia Ambarwati; Novi Lailiyul Wafiroh (J-MACC, 2024)
After the enactment of Law Number 6 of 2014 concerning Villages, the authority given to Village Governments became wider in managing their own households. This increasingly broad authority allows villages to receive funding channels from the Central Government called Village Funds. In managing these funds, the government has regulated it in Minister of Home Affairs Regulation Number 20 of 2018. This research aims to find out the role of village officials in accountability for managing village funds in Sumurgayam Village, Paciran District, Lamongan Regency, whether it is in accordance with Minister of Home Affairs Regulation Number 20 of 2018. The type of research used in this research is qualitative with a descriptive approach. The data used in this research is primary data in the form of interviews with village officials, namely the Village Head, Village Secretary, Village Treasurer, BPD, Hamlet Head and several Sumurgayam Village residents. The secondary data used by researchers is in the form of village archives, namely the RPJMDesa village profile and the Village Fund Budget Realization Report. The results of this research show that Sumurgayam village officials have played a role in accordance with Minister of Home Affairs Regulation Number 20 of 2018 starting from planning, implementation, administration, reporting, accountability to coaching and supervision. Accountability for managing village funds is in accordance with Minister of Home Affairs Regulation Number 20 of 2018, but in the process there are still village officials who do not understand some of their duties. Transparency in the management of Sumurgayam village funds has been fulfilled even though there are still people who do not understand its function.